Girls referred for amenorrhea: analysis of a patient series from a specialist center - Mörö, Sara; Kosola, Silja; Holopainen, Elina (Frontiers in Public Health, 2024)
Objective: Among adolescents, amenorrhea is a common reason for medical consultation. Despite the variety of underlying etiologies, the prevalence of the causes is incompletely understood. This study aimed to assess the demographic and etiological factors among patients with amenorrhea treated in a single specialist unit of adolescent gynecology.Design: Retrospective register study.Methods: Medical records of 438 girls evaluated for primary or secondary amenorrhea in a single tertiary care center between 2015 and 2019 were retrospectively reviewed. In all, 423 patients-171 with primary amenorrhea and 252 with secondary amenorrhea-were included in the study. Data on underlying conditions, anthropometric variables, and selected hormonal markers were analyzed.Results: Functional hypogonadotropic hypogonadism was the most frequent reason for primary (56%) and secondary (78%) amenorrhea. It was mostly explained by lifestyle-related functional hypothalamic amenorrhea caused by disordered eating, intense exercise, energy deficiency, psychological stress, and their combinations.Menstrual pattern is a significant indicator of overall health and well-being among adolescent girls and young women. Functional reasons behind primary and secondary amenorrhea are important to recognize. Treatment often requires long-term lifestyle modifications. The frequency of functional causes also implies that most amenorrhea cases are preventable.